The The Effect of Kangaroo Method Treatment (PMK) on Hypothermi Prevention on Low Birth weight in Bahagia Hospital Makassar - Surmayanti; Fitriana Jufri.P; A.Sri Hastuti Handayanti Usman (Politeknik Karya Persada Muna, 2021)
Background : He biggest on infant mortality is a problem that occurs in newborn or aged 0-28 days, Low Birth Weight (LBW) is one of the factors that has contributed to the cause of infant mortality, especially in the neonatal period. The Infant Mortality Rate (IMR) is a benchmark in determining the health status of a community, in the region. The purpose of this study was to determine the effect to Kangoroo Treatment Method (PMK) on the prevention of hypothermia in low birth weight infants at RSU Bahagia MakassarMethod : The type of research used was quasi-experimental. The population in all low weight babies born in May to July 2021. The sample in this study was all low birth weight newborns born in May to July 2021 totaling 22 babies. Result : There is a difference in the babys body temperature before and after with p < 0.001. Conclusion : Kangoroo Treatment Method (PMK) affects the babys body temperature, meaning that prevention and treatment of hypothermia can be done with PMK. Keywords: PMK, Hipotermi, BBLR